Pesantren dan Gairah Keislaman Kelas Menengah di Sumatera Barat - Fithri, Widia (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2019)
West Sumatra society today has a high interest in getting children into pesantren, it can be seen from the interest that increased every year. In terms of cost, education funds in pesantren are quite expensive. Admission fee into pesantren currently ranges from eight to fifteen million rupiahs, while monthly for one child ranges from seven hundred thousand to one million three hundred rupiahs per month. This differs greatly from public schools that are free of charge. The assumption is that this is a positive symptom where parents have a good Islamic passion and give sufficient attention to increase their children's religious understanding. This paper will explain about the phenomenon of education is quite expensive but able to attract the interest and attention of the community and reveal what factors are driving parents to enter children into Islamic boarding schools. The method used is qualitative. The fact that the assumption is not entirely true, because many factors that encourage parents to enter children into the pesantren are more driven by work, household problems, and more importantly, the community considers pesantren to be able to provide solutions for child development problems. In fact the pesantren is also unable to fully appreciate the role of parents. So the awareness of all parties, both parents and the school to collaborate, really helps the realization of better children's education